Gender Inequality in Social Security on the Basis of the ECtHR Case-Law - Oleg M. Yaroshenko; Kostiantyn Y. Melnyk; Dmytro Ð†. Sirokha; Olena S. Arsentieva; Irina I. Ð¢eslikova (Faculty of Law, Sriwijaya University, Indonesia, 2022)
As the European case-law shows, nowadays, there are numerous problems in the social sphere. Accordingly, there appears to be a need to study international regulation of equality and current social security problems to find possible solutions to the existing shortcomings and to strengthen human rights protection. The article aims to analyse the universal international regulation of equality and gender equality, in particular, and to study the problems of gender inequality in social security based on the European Court of Human Rights (ECtHR) case law to eliminate this discrimination. The leading research method is a legalistic one. It allowed us to analyse the international legislation on gender equality and to look into the ECtHR case law in gender discrimination in social security. It was found that gender inequality in social security is often a result of prior gender-based discrimination in labour relations. Despite the fact that legal acts protect women in cases of inequality, the analysis of the ECtHR case-law permitted us to conclude that men suffer from gender discrimination as much as women. Therefore, it is suggested to adopt legal acts on the equality of men and women in social security to overcome such discriminative practices at the legislative level. It is also recommended to implement the governmental policy on counteracting gender stereotypes in society. The research results can improve national legislation and international legal acts, further research into equality issues, and develop a methodological base for teaching human rights and social security.